Eucalyptus sp. at the Intersection of Environment and Culture in Kenya - Garrett Kluthe, Brandy M; Chen, Diana K (Ethnobiology Letters, 2017)
Members of the genus Eucalyptus are popular on small farms throughout Kenya, and include species such as Eucalyptus saligna, Eucalpytus globulus, and Eucalyptus grandis. Although they are fast-growing and perform well on marginal land, these trees are associated with negative environmental effects in Africa and elsewhere they have been introduced. In-person surveys were conducted with small farmers in Kenya to determine patterns of Eucalyptus sp. stand use and cultural importance. It was found that despite acknowledged short and long term environmental consequences, Eucalyptus sp. remains popular for medium term economic investment. These findings are consistent with other reports of Eucalyptus sp. woodlots serving as funding sources for education, health emergencies, etc., in parts of the world where bank loans are unavailable. Further, it was found that some farmers are using modified silviculture practices to ameliorate the negative effects of Eucalyptus sp., and others are seeking indigenous alternatives.